THE ROLE OF CORPORATE GOVERNANCE IN ENHANCING INVESTMENT ATTRACTIVENESS OF COMPANIES IN UZBEKISTAN (World Economics and Finance Bulletin, 2026)
Investment decisions are strongly influenced by how companies are managed and controlled, particularly in economies where institutional frameworks are still developing. In Uzbekistan, changes in corporate regulation and ownership structures have gradually shifted investor attention toward internal governance practices rather than solely financial indicators. This article examines the relationship between corporate governance quality and the investment attractiveness of companies operating in Uzbekistan. The analysis focuses on practical governance elements such as managerial accountability, consistency of decision-making processes, transparency in reporting, and the balance of interests between controlling and minority shareholders. The study argues that insufficient governance practices often increase perceived investment risks, even in financially stable firms. Conversely, companies demonstrating predictable management behavior and clear internal control mechanisms tend to attract greater investor interest. The findings indicate that improving corporate governance is not only a regulatory requirement but also a practical factor influencing long-term investment appeal in the Uzbek corporate sector
Keywords: corporate governance; investment attractiveness; management accountability